The Relationship Between Ego Identity and Hedonistic Lifestyle in Adolescents - Fajarista, Rahmadania; Taufik, Taufik (The Future of Education Journal, 2025)
This research is motivated by the hedonistic lifestyle being one of the phenomena that are often found in teenagers in the modern era. Hedonism that focuses on seeking pleasure and instant gratification is often influenced by social change, technological advances, and the influence of social media. Teenagers who adopt this lifestyle tend to prioritize excessive consumption, entertainment activities, and self-image in their social environment. However, behind the lifestyle that looks fun, the hedonistic lifestyle can also have negative impacts, such as ignoring personal responsibility, weak self-control, and limited development of authentic identity. Ego identity refers to stable self-awareness, including an understanding of the values, goals, and identity of an individual. In adolescents, the formation of ego identity is an important process that determines the direction of their development towards adulthood. This study aims to examine the relationship between the hedonistic lifestyle and the formation of ego identity in adolescents. This study aims to describe describe the picture of the hedonistic lifestyle in adolescents, describe the picture of ego identity in adolescents, and the relationship between the hedonistic lifestyle in adolescents and ego identity. This study uses a quantitative correlational method. This study involved 83 adolescents in Padang city using incidental techniques. The instruments used were a questionnaire on hedonistic lifestyle in adolescents and an ego identity questionnaire. Data analysis used percentage analysis techniques and was tested using the Pearson Product Moment correlation formula. The results of this study indicate that: (1) the average score of hedonistic lifestyle achievement in adolescents reached 88.16 (60.80) adolescents have a high hedonistic lifestyle, (2) the average score of ego identity achievement in adolescents reached 84.30 (64.85%) adolescents have low ego identity, and (3) there is a significant negative relationship between hedonistic lifestyle in adolescents and ego identity with a correlation of -0.007 and a significance value of 0.949. Thus, it can be interpreted that the higher the hedonistic lifestyle in adolescents, the lower their ego identity, conversely, adolescents with a weak hedonistic lifestyle tend to have a more developed ego identity.